Influence of the date of cut of rootstocks to the stub on growth of maider sour cherry trees cv. 'Łutówka' - Stanisław Wociór; Magdalena Kapłan; Salwina Palonka; Irena Wójcik (Acta Agrobotanica, 2013)
Over a three-year period (1997-1999) investigations were conducted on the effect of 6 date of cut to the stub on tree trunk diameter, height and branching of sour cherry maidens in the nursery.On the Prunus mahaleb seedling rootstock were found no significant influen ce of the date between January, 15 - March, 30 of cut to the stub on growth of sour cherry maidens cv. ´Łutówka' (tree trunk diameter and branching) and efficiency of nursery. The date of cutting in 15 April decreased trunk diameter and percent of the first quality trees.